Spatiotemporal variability and change in rainfall in the Oti River Basin, West Africa. Issue 3 (21st February 2022) - Kwawuvi, Daniel; Mama, Daouda; Agodzo, Sampson K.; Hartmann, Andreas; Larbi, Isaac; Bessah, Enoch; Limantol, Andrew Manoba; Dotse, Sam-Quarcoo; Yangouliba, Gnibga Issoufou
Abstract: Understanding rainwater dispersion in a spatiotemporal context is invaluable toward resourceful water management and a food-secure society. This study, therefore, assessed the variations in rainfall at a spatiotemporal scale in the Oti River Basin of West Africa for observed (1981–2010) and future periods (2021–2050) under the representative concentration pathways (RCPs) 4.5 and 8.5 emission scenarios. Rainfall data from meteorological stations and Climate Hazards Group Infrared Precipitation with Stations (CHIRPS) were used. The percentage changes in rainfall for the peak month as well as for rainy and dry seasons under the two climate scenarios were determined. The coefficient of variation (CV) and the standardized anomaly index (SAI) were used to assess annual variations in rainfall. In general, under both emission scenarios, rainfall is projected to decrease over the study area. However, the amount of rainfall during the peak month (August) for RCP4.5 and RCP8.5 could increase by 0.26 and 9.3%, respectively. The highest SAIs for the observed period were +1.58 (2009) and −2.29 (1983) with the latter showing a relationship with historic drought in the basin. The projected SAI under RCP4.5 and RCP8.5 indicated extremely wet (+2.12) and very wet (+1.91) periods for the years 2037 and 2028, respectively. The study provides relevant information and a chance to aid the design of innovative adaptation measures toward efficient water management and agricultural planning for the basin. HIGHLIGHTS: Spatiotemporal rainfall analysis was conducted over the Oti River Basin. The performance of climate models is improved when bias-corrected. Rainfall is projected to decrease in the basin. The decline in rainfall poses a threat to the livelihood of fringed communities. The Mann–Kendall test fostered knowledge of rainfall trends in the basin.